The legal status of consent to sexual intercourse: an Islamic dimension - Mohamad Yunus, Mohamad Ismail (The Law Society, International Islamic University Malaysia, 2002)
The most important element to constitute rape is the absence of consent on the part of the complainant. Unfortunately, it is noted that there is no spesific legal definition of consent found in any of the legislations dealing with rape. Basically, the prosecution must prove that during the particular time the complainant did not consent to the sexual penetration. Although previously, many cases of rape involved the use of force, violation and threat by the accused upon the complainant, but previously, in various modern and secular jurisdictions, this is no longer a legal requirement: it is the absence of consent on the part of the complainant which is the crux of the matter. It is admitted the notion of the consent is a difficult one to be legally defined and especially in rape, the concept gives rise to a number of different complex legal issues. Thus it is the objective of this paper to introduce some solutions and recommendations to the current legal issues by making references to the Islam's position on this matter.